PENGARUH TAX AVOIDANCE DAN BIAYA AGENSI TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN LQ45 - Warno, Warno; Fahmi, Ulul (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
This study aims to examine the influence of tax avoidance andcosts agencyon firm value and wants to test audit quality in strengthening and weakening the relationship between tax avoidance and firm value. The population in this study are companies listed in the LQ45 index in theEffect Exchange Indonesia2016-2018 period. Sampling in this study was carried out using purposive sampling with a total sample of 90 companies in a period of three years. This study uses a quantitative approach by using the SEM-PLS analysis method using WarpPLS 4.0 software. The results ofstudy this indicate that the variable tax avoidance that is projected using CashETR and agency costs projected with sales to total assets (STA) significantly influence the value of the company that is projected with Tobins'Q. The results of this study also show that the audit quality projected by bigfournot canweaken or strengthen the relationship that occurs between tax avoidance on firm value.